2018
DOI: 10.1039/c8nr04042g
|View full text |Cite
|
Sign up to set email alerts
|

Influence of particle size and shape on their margination and wall-adhesion: implications in drug delivery vehicle design across nano-to-micro scale

Abstract: Intravascular drug delivery technologies majorly utilize spherical nanoparticles as carrier vehicles. Their targets are often at the blood vessel wall or in the tissue beyond the wall, such that vehicle localization towards the wall (margination) becomes a pre-requisite for their function. To this end, some studies have indicated that under flow environment, micro-particles have a higher propensity than nano-particles to marginate to the wall. Also, non-spherical particles theoretically have a higher area of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
128
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 209 publications
(141 citation statements)
references
References 79 publications
2
128
0
1
Order By: Relevance
“…The effect of particle size on adhesion to cellular or synthetic surfaces under flow has been investigated in quite some depth . These studies have been generally performed with micron‐sized particles, thereby limiting comparisons to the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of particle size on adhesion to cellular or synthetic surfaces under flow has been investigated in quite some depth . These studies have been generally performed with micron‐sized particles, thereby limiting comparisons to the present study.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have been generally performed with micron‐sized particles, thereby limiting comparisons to the present study. In one study, adhesion of spherical particles to surfaces under flow was reported and the dependence of adhesion on size was nonmonotonic with 500 nm particles exhibiting maximum adhesion compared to 100 nm, 200 nm, and 2 ÎŒm particles . Mathematical models have also been reported to describe wall adhesion of particles under flow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, questions such as whether nanoscale particles exhibit margination qualitatively the same as microscale particle does still remains controversial. A recent effort by Cooley et al 30 using in vitro experiment and 2D in silico simulation to understand the cross-length-scale particle margination and adhesion propensity has set an example for a unified understanding of the nano-to-microscale particle dispersion in blood flows. However, the general physical mechanisms behind the multiscale particle dispersion/margination phenomenon in blood are still not presented; besides, the 2D simulation could still overlook the 3D nature of the tubular blood flow phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…cancer targeting, PS ranging from 100 to 300 nm is considered to be suitable as these particles can easily penetrate into the intracellular space [43]. Due to the presence of PEG chains at the surface of the nanoparticles, the outer layer of Labrasol Âź MTX-NLC is slightly lighter in color in comparison to olive oil MTX-NLC [44].…”
Section: Panda and Kuotsumentioning
confidence: 99%